Governance of Bojong Village, Bungbulang District, Garut Regency from the Perspective of Continuous Improvement (PDCA) - Lukman Nulmunir; Mulyaningsih; Aip Zaenal Mutaqin; Gugun Geusan Akbar (Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
This study aims to examine the implementation of Continuous Improvement (CI) within the Plan–Do–Check–Act (PDCA) framework at the village government level, focusing on governance, community engagement, and livelihood sustainability. The study employed a qualitative approach with an interpretive case study strategy, through document review and in-depth interviews. The results indicate that CI practices at the village level are contextual and adaptive, and most closely align with the incremental (Kaizen) approach that emphasizes incremental improvement, community participation, and continuous learning. The PDCA cycle serves as a reflective mechanism that allows village governments and communities to adjust policies and programs based on empirical evaluation and social feedback. Theoretically, these findings extend the study of CI in the local public sector by emphasizing its relevance to village governance. Practically, this study demonstrates that strengthening documentation, data-driven evaluation, and human resource capacity are key to CI sustainability at the village level.